Activated Endolysosomal Cation Channel TRPML1 Facilitates Maturation of α-Synuclein-Containing Autophagosomes - Pollmanns, Maike R.; Beer, Judith; Rosignol, Ines; Rodriguez-Muela, Natalia; Falkenburger, Björn H.; Dinter, Elisabeth (Frontiers in Cellular Neuroscience, 2022)
Background: Protein aggregates are degraded via the autophagy-lysosome pathway and alterations in the lysosomal system leading to the accumulation of pathogenic proteins, including aggregates of α-synuclein in Parkinson’s disease (PD). The importance of the endolysosomal transient receptor potential cation channel, mucolipin subfamily 1 (TRPML1) for the lysosomal function is highlighted by the fact that TRPML1 mutations cause the lysosomal storage disease mucolipidosis type IV. In this study, we investigated the mechanism by which activation of TRPML1 affects the degradation of α-synuclein. Methods: As a model of α-synuclein pathology, we expressed the pathogenic A53Tα-synuclein mutant in HEK293T cells. These cells were treated with the synthetic TRPML1 agonist ML-SA1. The amount of α-synuclein protein was determined by immunoblots. The abundance of aggregates and autolysosomal vesicles was determined by fluorescence microscopy and immunocytochemistry. Findings were confirmed by life-cell imaging and by application of ML-SA1 and the TRPML1 antagonist ML-SI3 to human dopaminergic neurons and human stem cell-derived neurons. Results: ML-SA1 reduced the percentage of HEK293T cells with α-synuclein aggregates and the amount of α-synuclein protein. The effect of ML-SA1 was blocked by pharmacological and genetic inhibition of autophagy. Consistent with TRPML function, it required the membrane lipid PI(3,5)P2, and cytosolic calcium. ML-SA1 shifted the composition of autophagosomes towards a higher fraction of mature autolysosomes, also in presence of α-synuclein. In neurons, inhibition of TRPML1 by its antagonist ML-SI3 blocked autophagosomal clearance, whereas the agonist ML-SA1 shifted the composition of a-synuclein particles towards a higher fraction of acidified particles. ML-SA1 was able to override the effect of Bafilomycin A1, which blocks the fusion of the autophagosome and lysosome and its acidification. Conclusion: These findings suggest, that activating TRPML1 with ML-SA1 facilitates clearance of α-synuclein aggregates primarily by affecting the late steps of the autophagy, i.e., by promoting autophagosome maturation. In agreement with recent work by others, our findings indicate that TRPML1 might constitute a plausible therapeutic target for PD, that warrants further validation in rodent models of α-synuclein pathology.